Sintesis dan Karakterisasi Nanokomposit Fe3O4/PANI sebagai Komponen Anoda Baterai - Balkis Br Harahap; Ridwan Yusuf Lubis; Abdul Halim Daulay (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Magnetic materials such as Fe₃O₄ have high potential as conductive materials and energy stores. However, its limited electrical properties require modification through the addition of conductive polymers to improve its performance. The combination of Fe₃O₄ and Polyanillin (PANI) is expected to improve conductivity and capacitance through the formation of Fe₃O₄/PANI nanocomposites. In this study, Fe₃O₄/PANI nanocomposites were synthesized using a co-precipitation method with local iron sand-based materials, then combined through an in situ polymerization method using aniline monomer volume variations of 4 mL, 6 mL, 8 mL, and 10 mL, coded PA1, PA2, PA3, and PA4, respectively. The results of characterization using X-Ray Diffraction (XRD) showed the formation of two main phases, namely magnetite (Fe₃O₄) and maghemite (γ-Fe₂O₃). Scanning Electron Microscopy (SEM) analysis showed that increased volume of aniline monomer resulted in a more homogeneous composite surface, although excessive volume led to overpolymerization. The test results using the LCR Meter showed an increase in capacitance and electrical conductivity values to reach optimal conditions in the PA3 sample, with a crystal size of 50.94 nm, capacitance of 8.9 F, resistance of 1.0 Ω, and conductivity of 127.4 S/m. These results prove that the variation in aniline monomer volume has a significant effect on the structural and electrical properties of Fe₃O₄/PANI nanocomposites. The optimum composition of PA3 shows high potential as an anode material or conductive energy storage electrode that supports the development of environmentally friendly and sustainable energy technology.